Greater residential greenness is associated with reduced epigenetic aging in adults - Andrey I. Egorov; Shannon M. Griffin; Jo Klein; Wei Guo; Jennifer N. Styles; Jason Kobylanski; Mark S. Murphy; Elizabeth Sams; Edward E. Hudgens; Timothy J. Wade (Scientific Reports)
Abstract Potential pathways linking urban green spaces to improved health include relaxation, stress alleviation, and improved immune system functioning. Epigenetic age acceleration (EAA) is a composite biomarker of biological aging based on DNA methylation measurements; it is predictive of morbidity and mortality. This cross-sectional study of 116 adult residents of a metropolitan area in central North Carolina investigated associations between exposure to residential green spaces and EAA using four previously developed epigenetic age formulas. DNA methylation tests of white blood cells were conducted using Illumina MethylationEPIC v1.0 assays. EAA values were calculated as residuals from the linear regression model of epigenetic age on chronological age. Residential greenness was characterized using tree cover, total vegetated land cover, and normalized difference vegetation index (NDVI) data. An interquartile range (IQR) increase in distance-to-residence weighted average greenness within 500 m of residence was consistently associated with a reduced EAA adjusted for sociodemographic covariates, smoking status, white blood cell fractions, and the two-dimensional spline function of geographic coordinates. The reduction in the EAA estimates for the four EAA measures ranged from − 1.0 to − 1.6 years for tree cover, from − 1.2 to − 1.5 years for vegetated land cover, and from − 0.9 to − 1.3 years for the NDVI; 11 of the 12 associations were statistically significant (p < 0.05). This study produced new evidence linking reduced epigenetic aging to greater greenness near residences.